Pharmacological approaches to the rational choice of combined mucoactive drugs - S. V. Okovity; V. S. Mar'yushkina; D. S. Sukhanov; N. O. Selizarova (Лечащий Врач, 2021)
The article analyzes the literature data and considers modern drugs of mucoactive therapy used for cough. The points of application and mechanism of action of the main groups of mucoactive drugs – expectorants, mucokinetics, mucoregulators and mucolytics are described. A parallel was drawn between the pharmacological effects of these groups of drugs and the pathogenetic mechanisms of inflammatory processes of the bronchial tree and increased bronchial secretion. It is shown that the most frequently used combinations are fixed expectorants with various active substances, expectorants and mucokinetics, as well as expectorants, mucokinetics and bronchodilators. The most frequent fixed combinations of expectorants are presented, as well as the composition of the main used mucoactive drugs. The use of rational combinations of mucoactive drugs in the management of cough can increase the effectiveness of pharmacotherapy, reduce the number of drugs used and the risk of side effects, and increase patient adherence to treatment.